1999
DOI: 10.1007/s004410051350
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing hormone-immunopositive nerve elements in apposition to chicken gonadotropin-releasing hormone I-containing perikarya in Japanese quail ( Coturnix coturnix japonica ) brain

Abstract: The neuroanatomic basis of how stress inhibits reproduction in birds is not understood. To address this question we used double-label immunofluorescence histochemistry to determine whether corticotropin-releasing hormone (CRH)-immunoreactive (ir) neuronal elements contact chicken gonadotropin-releasing hormone I (cGnRH I)-ir somata in brains of Japanese quail. The double-label system used a sheep anti-cGnRH I primary antibody with a secondary antibody conjugated to dichlorotriazinylaminofluorescein dihydrochlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
6
11
0
Order By: Relevance
“…The distribution of GnRH-ir neurons described for the septum closely matches the position of our LSc.vl, LSc.l, and CcS. This topographical assignment is corroborated by double-label data showing a close correspondence between GnRH-ir neurons and fibers immunoreactive for VIP and CRF (Teruyama and Beck, 2001;Wang and Millam, 1999). The CRF double-label data are particularly informative, as CRF-ir fibers in the present study were located only to the LSc.vl, LSc.l, and CcS.…”
Section: Histochemical Comparisons With the Major Septal Divisions Ofsupporting
confidence: 79%
“…The distribution of GnRH-ir neurons described for the septum closely matches the position of our LSc.vl, LSc.l, and CcS. This topographical assignment is corroborated by double-label data showing a close correspondence between GnRH-ir neurons and fibers immunoreactive for VIP and CRF (Teruyama and Beck, 2001;Wang and Millam, 1999). The CRF double-label data are particularly informative, as CRF-ir fibers in the present study were located only to the LSc.vl, LSc.l, and CcS.…”
Section: Histochemical Comparisons With the Major Septal Divisions Ofsupporting
confidence: 79%
“…Our preliminary data indicate that citalopram may act to increase serotonin release in the PVN and amygdala of stress-sensitive animals, which in turn would decrease CRF production. Earlier work demonstrated that CRF plays an anti-reproductive role in macaques (Ferin, 1995) and CRF may directly or indirectly inhibit GnRH neurons in the hypothalamus (Ferin, 1993, Polkowska and Przekop, 1997, Wang and Millam, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…One series of sections was immunostained for aromatase, one for gonadotropin-releasing hormone I (GnRH-I), and one for vasotocin under free-floating conditions, and then all were mounted on Superfrost slides. Immunostaining of aromatase, vasotocin, and GnRH-I followed published protocols employing the same antibodies (23)(24)(25). Control staining (using hypothalamic sections of other age-matched quails) omitting the primary antibody resulted in no cell labeling.…”
Section: Methodsmentioning
confidence: 99%